Fulfillment of the Constitutional Rights of Persons with Disabilities to Employment Opportunities in the Banking Industry of State-Owned Enterprises - Anggraini, Nastitie Kusuma; Susetyo, Heru (Journal of Law, Politic and Humanities, 2024)
Employment is one of many important aspect in the area of human rights protection. Indonesia’s citizens have the right to work and a decent livelihood, including people with disabilities. As one of the efforts to enhance opportunities to improve the welfare of persons with disabilities, Indonesian Law Number 8 of 2016 on Persons with Disabilities was formulated, which contains various arrangements regarding the rights of persons with disabilities and the State’s obligations to fulfill those rights. This study aimed to provide an overview of these regulation’s fulfillment, especially that related to equal employment opportunities for persons with disabilities, with a particular focus on the banking industry within SOEs. This study employs a non-doctrinal, descriptive-analytical approach to analyze Law No. 8/2016 on Persons with Disabilities, focusing on Article 53(1) regarding workforce representation in state-owned enterprises. Data is gathered through literature reviews and stakeholder interviews, using qualitative analysis to evaluate legal norms and provide a comprehensive understanding of the legal context. The finding revealed that the state plays a crucial regulatory role in protecting the rights of persons with disabilities, yet the implementation of Article 53(1) of Law No. 8/2016 has been inadequate, resulting in less than 0.5% representation in BUMN banks against the mandated 2%. To improve compliance, both the state and companies must prioritize recruitment and create inclusive opportunities for persons with disabilities.